Pathophysiology of interstitial vasomotricity: infarction of the adrenal gland - Stajano, Carlos; Scandroglio, Juan (Cirugía del Uruguay, 1973)
Clinical and physiopathological research resorts to experimentation in order to establish vasomoter fluxions of suprarenal gland when conditioned by polymorphous iraumatic aggression of distant origin. The source of reflex resolves round acute distensive injury caused by different processes of medica! or surgical pathology and its effects are felt in vasomotor field in intersticial site.